Prognostic impact of immune status and hematopoietic recovery before and after fludarabine, IV busulfan, and antithymocyte globulins (FB2 regimen) reduced‐intensity conditioning regimen (RIC) allogeneic stem cell transplantation (allo‐SCT). (27th January 2013) - Le, Amandine; Lestang, Elsa; Guillaume, Thierry; Delaunay, Jacques; Ayari, Sameh; Blin, Nicolas; Clavert, Aline; Tessoulin, Benoit; Dubruille, Viviane; Mahe, Beatrice; Roland, Virginie; Gastinne, Thomas; et al.
Abstract This retrospective analysis aimed to assess hematopoietic and immune recovery in a cohort of 53 patients [males: n = 33; median age: 59 yr (range: 22–70)] who received a FB2 (fludarabine 120–150 mg/m² + IV busulfan 6.4 mg/kg + antithymocyte globulin thymoglobulin 5 mg/kg) reduced‐intensity conditioning (RIC) allo‐stem cells transplantations (SCT). With a median follow‐up of 19 months (range: 2–53), the 2‐yr overall survival, disease‐free survival (DFS), relapse incidence, and non‐relapse mortality were 63%, 59.5%, 35%, and 6%, respectively. In univariate analysis, the factors correlated with a significantly higher 2‐yr OS and DFS were a higher total circulating lymphocytes count at transplant (>730/mm3; OS: 81% vs. 43%, P = 0.02; DFS: 73% vs. 45.5%, P = 0.03) and a higher recovery of leukocytes (>5300/mm3) (2‐yr OS: 81% vs. 44%, P = 0.007; 2‐yr DFS: 72% vs. 46%, P = 0.08), neutrophils (>3200/mm3) (2‐yr OS: 76% vs. 50%, P = 0.03; 2‐yr DFS: 67% vs. 52.0%, P = 0.1), and monocytes (>590/mm3; 2‐yr OS: 80% vs. 45%, P = 0.004; 2‐yr DFS: 76% vs. 42%, P = 0.01) at day +30 post‐transplant. In multivariate analysis, the only independent factors associated with a significantly higher OS and DFS were a better immune status at transplant (lymphocytes count >730/mm3) and a higher monocytes count (>590/mm3) at day +30 post‐transplant. These results suggest that immune status and hematopoietic recovery before and after FB2 RIC allo‐SCT can be significant predictors of outcome. This paves the way for future studies aiming to closely monitor the kinetics of immune recovery after RIC allo‐SCT and to evaluate the impact of growth factors and other immunostimulatory cytokines in the setting of RIC allo‐SCT.